2019
DOI: 10.1590/0034-7167-2018-0586
|View full text |Cite
|
Sign up to set email alerts
|

Community interventions related to intimate partner violence among adolescents: scope review

Abstract: Objective: To map the successful experiences of interventions aimed at coping with violence among intimate partners in adolescence, in the light of the gender and generation categories. Method: Scope review carried out in the MEDLINE, CINAHL, Scopus and PsycINFO databases. We selected primary, empirical, quantitative and qualitative studies published in three languages. Results: From the 3,234 articles found, 31 made up the review. Most of the interventions were carried out at the school level, with focus of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 41 publications
0
14
0
5
Order By: Relevance
“…By analyzing the results in the light of the generation analysis category (13) , it is possible to understand that it determines the social space occupied by the adolescents and the construction of a polarized relationship between them and the participants in the study. adolescents and adults impossible (6) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By analyzing the results in the light of the generation analysis category (13) , it is possible to understand that it determines the social space occupied by the adolescents and the construction of a polarized relationship between them and the participants in the study. adolescents and adults impossible (6) .…”
Section: Discussionmentioning
confidence: 99%
“…VPI in adolescence is determined by generational, historical, economic issues and, above all, by the experience of gender roles that polarize different tensions for the genders, such as the production and reproduction of socially accepted models (5) . Also, further difficulties are driven by generational issues that adolescents encounter in accessing the health services (6)(7) .…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that poverty, lack of education and food security is associated with IPV during and after pregnancy (30,31). Appropriate interventions have been shown to help minimize and control IPV as various experiments demonstrated this in several countries (32).…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that poverty, lack of education and food security is associated with IPV during and after pregnancy (30,31). Appropriate interventions have been shown to help minimize and control IPV as various experiments demonstrated at in several countries (32).…”
Section: Discussionmentioning
confidence: 99%